Factors Affecting the Gross Mortality Rate (GDR) and Net Death Rate (NDR) in Hospital - Lutfi Mar’atin; Riska Rosita; Reza Melina Ningtyas (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
Hospital statistics on patient mortality rates are needed to assess the quality of hospital services. This study aims to determine the factors that influence the Gross Mortality Rate and Net Mortality Rate. The research method used is a literature study. Data analysis was carried out by extracting data and synthesizing data from the various previous research literature. The results showed that the Gross Mortality Rate and Net Mortality Rate changed from year to year, either decreasing or increasing. The factors that influence it are the severity of the disease, facilities and infrastructure, the availability of medical personnel, the performance of health services, and the accuracy of therapy or treatment. The conclusion is that the calculation of the GDR and NDR statistics can be an evaluation of the quality of hospital services. Therefore, hospitals must carry out internal evaluations regularly to reduce the Gross Mortality Rate and Net Mortality Rate so that they can be used in making decisions for hospitals.